Docosahexaenoic acid normalizes QT interval in long QT type 2 transgenic rabbit models in a genotype-specific fashion. Issue 3 (3rd October 2021) - Castiglione, Alessandro; Hornyik, Tibor; Wülfers, Eike M; Giammarino, Lucilla; Edler, Iask; Jowais, Jessica J; Rieder, Marina; Perez-Feliz, Stefanie; Koren, Gideon; Bősze, Zsuzsanna; Varró, András; Zehender, Manfred; et al.
Abstract: Aim: Long QT syndrome (LQTS) is a cardiac channelopathy predisposing to ventricular arrhythmias and sudden cardiac death. Since current therapies often fail to prevent arrhythmic events in certain LQTS subtypes, new therapeutic strategies are needed. Docosahexaenoic acid (DHA) is a polyunsaturated fatty acid, which enhances the repolarizing IKs current. Methods and results: We investigated the effects of DHA in wild type (WT) and transgenic long QT Type 1 (LQT1; loss of IKs ), LQT2 (loss of IKr ), LQT5 (reduction of IKs ), and LQT2–5 (loss of IKr and reduction of IKs ) rabbits. In vivo ECGs were recorded at baseline and after 10 µM/kg DHA to assess changes in heart-rate corrected QT (QTc) and short-term variability of QT (STVQT). Ex vivo monophasic action potentials were recorded in Langendorff-perfused rabbit hearts, and action potential duration (APD75 ) and triangulation were assessed. Docosahexaenoic acid significantly shortened QTc in vivo only in WT and LQT2 rabbits, in which both α- and β-subunits of IK s -conducting channels are functionally intact. In LQT2, this led to a normalization of QTc and of its short-term variability. Docosahexaenoic acid had no effect on QTc in LQT1, LQT5, and LQT2–5. Similarly, ex vivo, DHA shortened APD75 in WT and normalized it in LQT2, and additionally decreased AP triangulation in LQT2. Conclusions: Docosahexaenoic acid exerts a genotype-specific beneficial shortening/normalizing effect on QTc and APD75 and reduces pro-arrhythmia markers STVQT and AP triangulation through activation of IKs in LQT2 rabbits but has no effects if either α- or β-subunits to IKs are functionally impaired. Docosahexaenoic acid could represent a new genotype-specific therapy in LQT2.